Understanding microRNA biogenesis and function through annotation of primary miRNA transcripts and characterization of functional interactions between microRNAs and RNA-binding proteins - Haskell, Dustin (Kansas State University, 2021)
The gene expression programs that establish and maintain cellular and organism homeostasis require precise, potent, and multifaceted forms of regulation. Post-transcriptional mechanisms of regulation rely on the combinatorial action of two major classes of effectors: RNA-binding proteins (RBPs) and microRNAs (miRNAs). miRNAs are small noncoding RNAs that interact with many developmental and cellular pathways by repressing gene targets and are therefore critical to the execution of gene expression programs. miRNA dysfunction can lead to widespread disruption of gene regulatory networks, contributing to the occurrence and progression of developmental disorders and pathologies such as cancer. Most miRNAs are generated through a complex biogenesis that includes RNA Pol II-dependent transcription, successive enzymatic processing by endonucleases DRSH-1 and DCR-1 and loading into Argonaute proteins to form the miRNA induced silencing complex (miRISC). Guided by the loaded miRNA, miRISC binds the 3'UTR of a target mRNA and actively downregulates its expression through translation repression or mRNA degradation. Mature miRNAs are produced through a series of enzymatic processing steps. Initial processing of primary miRNA gene transcripts (pri-miRNAs), performed by endonuclease DRSH-1, often occurs co-transcriptionally or shortly thereafter. Hence, pri-miRNA transcripts are largely absent from traditional RNA sequencing data sets, and thus difficult to characterize. The lack of primary miRNA annotations has hindered efforts to understand the mechanisms that modulate miRNA gene expression and complicated our ability to study the regulation of pri-miRNA processing. To fill this gap, we used an auxin-induced degron system to conditionally deplete DRSH-1 and greatly reduce processing of pri-miRNAs, leading to their accumulation. Subsequent RNAseq experiments identified pri-miRNAs and allowed for their annotation, revealing previously unappreciated, complex genomic features of the miRNA loci and providing an essential resource for future studies of miRNA regulation. In addition, we identified >300 novel transcripts, uncovering existence of previously uncharacterized RNAs that may depend on DRSH-1 for processing, thus expanding the known C. elegans transcriptome. Once miRNAs are processed to their mature form, they exert their repressive functions by targeting miRISC to the 3’ UTRs of mRNA transcripts through partial base-pair complementarity. RBPs represent an important class of molecules that contribute to post-transcriptional regulation of gene expression, however, the extent of functional RBP coordination with miRNAs is largely unexplored. Similarly, a comprehensive understanding of how RBPs coordinate with miRNAs to regulate gene expression is lacking. To address the potential functional interaction between miRNAs and RBPs, I performed a targeted RNAi screen of 27 K-homology (KH) domain RBPs to identify factors that genetically interact with five miRNA sensitized mutant backgrounds. I identified multiple KH domain RBPs that functionally interact with all or some of miRNAs families tested, expanding our understanding of the crosstalk between two classes of post-transcriptional gene regulators. Overall, this work has expanded our understanding of miRNA gene structure and the characteristics of primary miRNA transcripts, ultimately providing a valuable tool for future study of pri-miRNA transcription and processing. Furthermore, this work established a functional relationship between several RNA-binding proteins and developmental miRNA pathways, thus identifying candidates for future studies of functional RBP-miRNA interactions.
Keywords: microRNA; C. elegans; Regulation of gene expression